2016
DOI: 10.1080/14712598.2016.1195364
|View full text |Cite
|
Sign up to set email alerts
|

Designing multivalent proteins based on natural killer cell receptors and their ligands as immunotherapy for cancer

Abstract: Introduction Natural killer (NK) cells are an important component of the innate immune system that play a key role in host immunity against cancer. NK cell recognition and activation is based on cell surface receptors recognizing specific ligands that are expressed on many types of tumor cells. Some of these receptors are capable of activating NK cell function while other receptors inhibit NK cell function. Therapeutic approaches to treat cancer have been developed based on preventing NK cell inhibition or usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Additional components can be added to manipulate the immune synapse between NK cells and their targets. Some have suggested that engaging NKG2D through fusion proteins (Smits et al 2016, von Strandmann et al 2006) may be more advantageous. In addition, scFvs that block NK cell-specific or broad checkpoints like KIRs, TIGIT, NKG2A, or PD1 may be optimal.…”
Section: Bispecific and Trispecific Killer Cell Engagersmentioning
confidence: 99%
“…Additional components can be added to manipulate the immune synapse between NK cells and their targets. Some have suggested that engaging NKG2D through fusion proteins (Smits et al 2016, von Strandmann et al 2006) may be more advantageous. In addition, scFvs that block NK cell-specific or broad checkpoints like KIRs, TIGIT, NKG2A, or PD1 may be optimal.…”
Section: Bispecific and Trispecific Killer Cell Engagersmentioning
confidence: 99%
“…by targeting NKG2D-L with chimeric antigen receptor T (CAR-T) cells (NKR-2) (NCT03018405), (CYAD-02) (NCT04167696). Other promising constructs which utilize the extracellular domain of NKG2D to target NKG2DL expressed on various tumors are NKG2DL-targeted Bispecific T-cell Engagers (NKG2D-BiTE) (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…NKG2D and its ligands are recognized as modulators of tumor immunity and as such of interest to cancer immunotherapy [43] , [44] , [45] , [46] . Among current approaches are the development of multivalent immunoligands containing MICA or ULBP2 for stimulation of T cell and NK cell NKG2D [47] , [48] , [49] and pharmacological enhancement of NKG2D ligand expression [50] .…”
Section: Discussionmentioning
confidence: 99%